BIOM-04. SENSITIVE DETECTION OF LEPTOMENINGEAL DISEASE USING CELL-FREE DNA FROM CEREBROSPINAL FLUID. (12th November 2021) - White, Michael; Klein, Robert; Shaw, Brian; Kim, Albert; Subramanian, Megha; Mora, Joana; Giobbie-Hurder, Anita; Nagabhushan, Deepika; Jain, Aarushi; Singh, Mohini; Kuter, Benjamin; Nayyar, Naema; et al.
Abstract: Leptomeningeal disease is a devastating complication of cancer that is frequently underdiagnosed due to the low sensitivity of cerebrospinal fluid cytology, the current gold-standard diagnostic method. We performed genomic sequencing on cerebrospinal fluid specimens obtained from patients with suspected or confirmed leptomeningeal disease to identify tumor-derived cell-free DNA. From the same fluid draw, cerebrospinal fluid cytology was assayed for comparison. 30 patients underwent cytology and cell-free DNA analysis. This study consisted of two patient populations: 22 patients with cytology-confirmed leptomeningeal disease without parenchymal tumors abutting their cerebrospinal fluid and 8 patients with parenchymal brain metastases with no evidence of leptomeningeal disease. The primary outcome was the diagnostic accuracy of cell-free DNA, defined as the number of correct diagnoses out of the total number of tests assayed. A total of 30 patients, 23 female and 7 male, with a median age of 51 participated in this study. Participants mostly presented with metastatic solid malignancies. In patients previously diagnosed with leptomeningeal disease via cytology with no parenchymal tumor abutting cerebrospinal fluid, cell-free DNA was accurate in diagnosis of leptomeningeal disease in 45 of 48 follow-up samples (94%; 95% CI, 83%-99%). Cytology was accurate in 36 of 48 follow-up samples (75%; 95% CI, 60%-86%). Cell-free DNA was significantly more accurate (P=.02) and sensitive (P=.02) than cytology in patients without parenchymal tumors abutting the cerebrospinal fluid. In three patients with parenchymal brain metastases abutting the cerebrospinal fluid and no suspicion for leptomeningeal disease, cytology was negative in all three patients; whereas, cell-free DNA was positive in all three. This study demonstrates the improved sensitivity and accuracy of cell-free DNA in diagnosing leptomeningeal disease with the exception of parenchymal tumors abutting cerebrospinal fluid. Overall, these results will lead to improved diagnosis of leptomeningeal disease and potentially earlier intervention and clinical trial enrollment.